Determination of Heavy Metal Content (Cd, As) in Fish Widely Consumed in East Coast of Peninsular Malaysia - Razak, Shariza Abdul (Universiti Sains Malaysia, 2009)
South China Sea is an important source of marine fishes used as food to the population in the East Coast of Peninsular Malaysia (Kelantan, Terengganu and Pahang). Recent fast pace of development contributed to the pollution to the marine ecosystem as well as marine fishes in this area. In this study, heavy metals (Cd and As) were analysed in the popular and widely consumed fish ( Selar boops, Rastrellinger branchysoma, Decapterus maruadsi and Sardinella sirm) by Atomic Absorption Spectrometry (AAS). The average metal concentration of Cd ranging from 0.05-6.93 mg/kg and highest concentration was found in the organ and lowest in the muscle. Concentration of As is in the range of 0.01-0.07 mg/kg and distributed evenly in muscle, bones and internal organ (livers). From this study, it might indicate that the fishes are still safe for consumption but caution must be adhered in order to reduce pollution in this sea.